Innovative circular path harvester for mechanical harvesting of irregular and large-canopy olive trees - Sola-Guirado, Rafael R.; Blanco-Roldan, Gregorio L.; Castro-Garcia, Sergio; Castillo-Ruiz, Francisco J.; Gil-Ribes, Jesús A. (International Journal of Agricultural and Biological Engineering, 2018)
The harvesting process of the olive tree is mainly performed by manual means, because traditional olive orchards (the main planting typology) are formed of irregular, large-canopy trees that are very difficult to harvest mechanically. For that reason, the cost of harvesting is very high, and it threatens the future of these plantations whose conversion to other more modern layouts is not always possible due to several limitations. The introduction of a harvester may represent the technological change that is the key factor for improved competitiveness. The main purpose of this work was to develop a harvester based on canopy shaker technology for work on irregular, large trees in a circular path. The design of the harvester was based on a determination of tree geometry, together with tree training. Field tests were used to determine machine-tree interaction, and to evaluate the removal, catch frame and driven systems. The proposed innovation allowed the fully mechanical harvest of previously planted trees with a removal efficiency of over 84%, achieving an effective field capacity of 0.21 hm2/h. Although the results so far have been promising, further improvements are advisable in machine and tree adaptation. Keywords: olive tree, olive fruit, canopy shaker, harvester, machinery design DOI: 10.25165/j.ijabe.20181103.3265 Citation: Rafael R. Sola-Guirado, Gregorio L. Blanco-Roldan, Sergio Castro-Garcia, F.J. Castillo-Ruiz, Jesus A. Gil-Ribes. Innovative circular path harvester for mechanical harvesting of irregular and large-canopy olive trees. Int J Agric & Biol Eng, 2018; 11(3): 86–93.